Early fattening and improving feeding quality of Kejobong goats could reduce methane production and improve meat production - Restitrisnani, V.; Pangestu, E.; Rianto, E.; Kurihara, M.; Nabila, F.; Adiwinarti, R.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2022)
An experimental study was carried out to evaluate the implication of early fattening of Kejobong goats by improving feeding quality on methane production and meat production. Sixteen goats (8 young and 8 mature) were raised for 4 months study period. Nested design was used in this study, with young and mature as a nest factor, and diet (G7C3: 70% grass and 30% concentrate and G3C7: 30% grass and 70% concentrate) as the treatments. The main parameters observed were DMI, BWG, carcass (CWG) and meat weight gain (MWG), and methane emission. The results showed, the young goat fed G3C7 was higher than that fed G7C3 in DMI. The BWG’s of goats fed G3C7 were higher than those fed G7C3, but there was no difference between ages in BWG. The FCR of young goat fed G3C7 was lower than that fed G7C3. The DMI of mature goat was higher than young goat, but there were no differences between the ages in DM digestibility, carcass weight and meat weight gain. The young and mature goats fed G3C7 was significantly lower than that of G7C3 in methane emissions per unit of BWG (0.28 vs 0.40 and 0.36 vs 0.53, respectively), in methane emissions per unit CWG (0.60 vs 0.93 and 0.79 vs 1.47, respectively), and methane emission per unit MWG (0.89 vs 1.42 and 1.16 vs 2.19, respectively). It can be concluded that fattening young Kejobong goats by improving feed quality is more environmentally friendly than fattening the mature ones.